How do Children Learn Mathematics? An Exploration into Mathematics Classroom Processes at Secondary Schools of Bhubaneswar - Krishnan, Dhanya; Kapoor, Saurabh (JOURNAL OF INDIAN EDUCATION, 2019)
Considering the change in the perception of mathematics classrooms of India after the emergence of NCF-2005, which emphasises on mathematisation, it is significant to examine mathematics classroom processes. Four secondary schools from Bhubaneswar that are affiliated to CBSE had been selected for the present study. Data was collected using teacher questionnaire, classroom observation and Focus Group Discussion with students. Curricular contents in Mathematics prescribed for Class IX are found quite appropriate, grade specific and properly sequenced as expressed by the teachers. Geometry concepts especially related to Euclidean Geometry are difficult to transact as teachers and students faced problems in understanding these concepts. Although, the resource materials, such as mathematics lab and mathematics kits are available in the majority of schools, their inadequacy from the viewpoint of a large number of students and lack of physical space for storage and use are quite staggering. The preparation of lesson plans/notes in mathematics is more ritualistic than having any serious and practical pedagogical concern. Methods appropriate to the content and the level of students were found to be used frequently or sometimes by maximum teachers while teaching mathematics. No group activities were conducted and rarely any individual activity took place.